Retreatability of Root Canals Obturated Using Gutta-Percha with Bioceramic, MTA and Resin-Based Sealers - Uzunoglu, Emel; Yilmaz, Zeliha; Deniz Sungur, Derya; Altundasar, Emre (Iranian Endodontic Journal, 2015)
Introduction: The aim of this study was to evaluate the retreatability of root canals obturated with gutta-percha (GP) and three different endodontic sealers [iRoot SP (bioceramic sealer), MTA Fillapex (MTA-based sealer) and AH-26 (epoxy resin-based sealer)] using the ProTaper Universal Retreatment (PTR) system. Methods and Materials: Forty extracted single-rooted human teeth were prepared with universal ProTaper files up to F4 (40/0.06). Specimens were randomly divided into four groups according to obturation technique/material: single-cone GP/AH-26, lateral compaction of GP/AH-26, single-cone GP/iRoot SP, and single-cone GP/MTA Fillapex. Root fillings were removed with PTR. The time taken to reach the working-length (TWL) was recorded. Roots were longitudinally sectioned and each half was evaluated using a stereomicroscope. Three observers scored each third of all specimen. Obtained data were analyzed using the Kruskal-Wallis, Mann-Whitney U, Welch and Games-Howell tests. The level of significance was set at 0.05. Results: In single-cone GP/MTA Fillapex group the TWL was significantly shorter. The remnant of filling material in the apical and middle thirds of groups was similar and higher than the coronal thirds. Conclusion: None of the tested sealers were completely removed from the root canal system